The presence and impact of different board characteristics on the performance of the private companies in Kosovo - Merita, Gjyshinca Peja (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2025)
In the recent years, corporate governance has garnered significant attention, evolving into a notable topic for discussion. Over the past decade, the behaviour and conduct of boards of directors have taken an extraordinary dimension. Moreover, the unpredicted and unprecedented outbreak of the COVID-19 pandemic underscored the significance and the role of the business leaders, especially of the boards of directors. The purpose of this research is to study the presence and influence of various board characteristics on the performance of private companies in Kosovo. The research explores the relationship between board presence, board size, board independence, board composition, gender diversity, and the performance of these private companies in Kosovo. The research uses a quantitative approach, surveying large and medium-sized companies. A sample of 61 companies was selected to examine the correlation between board characteristics and company performance indicators such as Return on Equity (ROE), sales and profit. The findings show that 70% of the companies in the study have a board of directors. The results indicate that the presence of a board, as a proxy for adopting corporate governance practices, has a positive and significant impact on company performance. However, these boards often lack independence, being largely dominated by family members. Furthermore, gender diversity is limited, with women occupying only 17% of the total board seats. This research is expected to serve as a valuable guide and practical reference for policymakers, company owners, boards of directors, and top management teams, to comprehensively assess and facilitate improvement of the understanding of corporate governance in Kosovo.